From BRICS to BRICS+: Sheer More Members is not a Challenge to G7 - Katrin Kamin; Rolf J. Langhammer (The Economists' Voice, 2023)
The global economic landscape is undergoing a transformative shift, as evidenced by the BRICS nations' increasing dominance. This development raises questions about the emergence of economic and political blocks and their potential leverage. China and India, as the world's most populous nations within the group, are instrumental in driving global economic demand. The expansion of BRICS, with new members possessing vast natural resources, amplifies the group's influence. However, the BRICS face a monetary and financial Achilles heel, especially in the case of China, hindering their ability to act independently. As the BRICS gain geopolitical significance, the G7 responds with infrastructure initiatives and trade agreements, though success hinges on reciprocal concessions. The BRICS thus serve as a wake-up call for the G7, prompting considerations of rejuvenating political and economic links amidst a shifting global landscape.
Keywords: F02; F15; F36; F40; F59; 330; BRICS+; global order; International Trade; strategic resources; Monetary Policy